2019
DOI: 10.1038/s41416-019-0507-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic molecular comparison of primary versus metastatic pancreatic tumours

Abstract: BACKGROUND: Molecular profiling is increasingly used to match patients with metastatic cancer to targeted therapies, but obtaining a high-quality biopsy specimen from metastatic sites can be difficult. METHODS: Patient samples were received by Perthera to coordinate genomic, proteomic and/or phosphoproteomic testing, using a specimen from either the primary tumour or a metastatic site. The relative frequencies were compared across specimen sites to assess the potential limitations of using a primary tumour sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Mutational and transcriptional changes in some of the significant genes in Table 2 have previously been shown to be associated with PDAC. Brar et al (2019) 34 found that LRP1B (low-density lipoprotein receptor-related protein 1B) mutations are more frequent in metastatic lesions than in primary pancreatic tissue suggesting that mutation in this tumor suppressor gene may promote PDAC metastasis.…”
Section: The Relevance Of Significant Genes By Association Testmentioning
confidence: 99%
“…Mutational and transcriptional changes in some of the significant genes in Table 2 have previously been shown to be associated with PDAC. Brar et al (2019) 34 found that LRP1B (low-density lipoprotein receptor-related protein 1B) mutations are more frequent in metastatic lesions than in primary pancreatic tissue suggesting that mutation in this tumor suppressor gene may promote PDAC metastasis.…”
Section: The Relevance Of Significant Genes By Association Testmentioning
confidence: 99%
“…Integration of genomic and transcriptional features in pancreatic cancer revealed that cell cycle progression was increased in PDAC metastases with driver gene ( KRAS , TP53 , CDKN2A , SMAD4 ) loss [ 28 ]. Moreover, mutations in known driver genes in the metastases of individual patients with PDAC were remarkably uniform [ 29 ], and no significant differences were identified at the gene or pathway level when comparing genomic alterations between primary and metastatic pancreatic tumors [ 30 ]. Many studies have reported some genes which may be involved in tumor metastasis, such as KAI1 and nm23-H1 in pancreatic cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other organ-specific diseases, such as chronic pancreatitis, pancreatic duct obstruction, jaundice, and diabetes, may confound the performance of a protein biomarker in pancreatic cancer detection. Composite markers or scores, focusing on multi-omics approaches [ 147 ] with the concomitant application of computational biology and artificial intelligence principles, can enhance detection accuracy and provide a better robustness. These panels of markers can be initially tested in high-risk patients (smokers, chronic pancreatitis, mucinous neoplasms of the pancreas, and genetic predisposition) before being validated in lower risk patients [ 148 , 149 , 150 ].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%